Respiratory Contagion - Pokorski, Mieczyslaw (Neuroscience and Respiration, 2016)
The book focuses on the contagion nature of respiratory ailments, the ways a pulmonary disease is spread. Respiratory infections are surrounded by interrelated circumstances that act upon individual and community and eventually underlie morbidity. Patient's age, vulnerability to infections, immune function and responses, comorbidities, but also medical care and the agility in coping with stress, are just a few basic determinants of a diseased state. Modern medication, like newfangled antibiotics and their unrestrained use, may not guarantee the best solution to patient's condition. A valuable asset of this book is a blend of personal experience and expertise of contributors in pursuit of finding new solutions to old clinical problems. The book will be of interest to clinicians, researchers, health care providers, and other health care professionals, particularly those dealing with contagious diseases.